RANCANG BANGUN BUKU AJAR ELEKTRONIK INTERAKTIF GELOMBANG BUNYI UNTUK MELATIH KESEIMBANGAN LITERASI SAINS - Syafiq AL-B (2023)
Physics teaching materials with unidirectional learning content are often the difficulties faced by students when studying physics independently. Thus, students need a teaching material that supports understanding of the subject matter. This study aims to produce sound wave interactive electronic textbooks to train the balance of scientific literacy so that they are able to support students' independent learning of sound wave material. The research method used is a mixed method with an exploratory sequential design. The initial stage of this research is qualitative data collection. The results of the qualitative data obtained are used to design interactive electronic textbooks. The next stage is validating interactive electronic books and processing them quantitatively. Then a limited trial was carried out on students to obtain data in the form of increased learning outcomes, book readability, and student responses. From these stages, the results showed that there was an increase in the cognitive ability and balance of students' scientific literacy, including the quite effective category with an N-gain of 67.48%, an average readability level of 77.6%, including the high category, and a positive response from students. The final stage of this research is to revise the interactive electronic books, so that the research objectives are achieved, namely the results of the design of interactive electronic books that balance the aspects of scientific literacy with a ratio of 38% : 21% : 22% : 19%. This research is useful for students to improve cognitive understanding and the balance of students' scientific literacy in understanding sound waves independently.